ANALISIS BIAYA PRODUKSI DAN EFISIENSI PRODUKSI USAHATANI PADI SAWAH DI KECAMATAN BANTAN KABUPATEN BENGKALIS - Marida Marida; Syaiful Hadi; Novian Novian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The research carried out on wetland rice in Bantan District of Bengkalis District aims to analyze whether farmers have implemented cultivation technique according to recommendations from agricultural extension officers, analyzed wetland farming and analyzed the production efficiency of weatland rice farming in Bantan District. The methode used is critical analysis method, cost analysis and DEA analysis. Th enumber of respondents in this reset were 45 racial farmers. From the results of the research that has been done, it is know that the farmers of rice paddies in bantan district before carry out rice cultivation according to the recommendations of the extension workers, and for the total average production costs that must be spent by farmers for a planting period of Rp 20.197.156/ Ha receipts od Rp 23.323.721/ Ha. The net income received by farmers is Rp 3.126.768/ Ha with an RCR value of 1.17 while for the analysis of its own production efficiency the average farmers has not been technically, allocatively and economically efficient. Key Words: Weatland Rice, Production Efficiency, Farmers